Wireless communication system with frequency selective channel OFDM modulation technique - Hayder Al Ibraheemi; Mazen M. A. Al Ibraheemi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper introduces the design and implementation of a wireless communication system with MATLAB based on orthognal frequency division multiplexing technique (OFDM). The constructed system is consisting of transmitter, fading channel and receiver. At the transmitter, the transmitted signal first modulated with PSK modulation, and then multiplexed with OFDM technique to achieve a higher bit rates transmission. The signal was then transmitted through a frequency selective channel with 6 taps. In the receiver parity. The received faded signal processed to be de-multiplexed and de-modulated. Then, a frequency domain equalizer was adopted to remove the fading noise and the inter-symbol interference from the received signal that introduced due to the fading channel. In order to inspect the performance of the frequency equilizer, bit error rate for the overall system was calculated at the receiving point and to recover the original information signal. The simulation results of the designed system as well as the frequency equilizer showed a robustness against the frequency selective faded channel effects. The maximum obtained bit error rate was around 10-5, which means that original signal was effectively recovered.